Impact on continuity of care of decentralized versus partly centralized mental health care in Northern Norway - Myklebust, Lars Henrik Ryther; Olstad, Reidun E.; Bjorbekkmo, Svein; Eisemann, Martin; Wynn, Rolf; Sørgaard, Knut (University of Utrecht, 2011)
The issue of continuity of care is central in contemporary psychiatric services research. In Norway, inpatient admissions are mainly to take place locally, in a system of small bed-units that represent an alternative to traditional central psychiatric hospitals. This type of organization may be advantageous for accessibility and cooperation, but has been given little scientific attention. To study whether inpatients’ utilization of outpatient services differ between an area with a decentralized care model in comparison to an adjacent area with a partly centralized model. The study was based on data from a one-year registered prevalence sample, drawing on routinely sampled data supplemented with data from medical records. Service-utilization for 247 inpatients was analyzed. The results were controlled for diagnosis, demographic variables, type of service system, localization of inpatient admissions, and length of hospitalization. Most inpatients in the area with the decentralized care model also utilized outpatient consultations, whereas a considerable number of inpatients in the area with a partly centralized model did not enter outpatient care at all. Type of service system, localization of inpatient admission, and length of hospitalization predicted inpatients’ utilization of outpatient consultations. The results are discussed in the light of systems integration, particularly management-arrangements and clinical bridging over the transitional phase from inpatient to outpatient care. Inpatients’ utilization of outpatient services differed between an area with a decentralized care model in comparison to an adjacent area with a partly centralized care model. In the areas studied, extensive decentralization of the psychiatric services positively affected coordination of inpatient and outpatient services for people with severe psychiatric disorders. Small, local-bed units may therefore represent a favourable alternative to traditional central psychiatric hospitals.